Design of Automatic Fire Fighting Systems on the Basis of Oscillating Monitors - Ignatov А. В.; Potekha Алексей Валентинович; Potekha Валентин Леонидович (Chrezvychaynye situatsii: obrazovanie i nauka, 2006)
The authors of the article examine the problems of design of fire fighting systems on the basis of automatic oscillating monitors. The authors present specific data for the design of an automatic fire fighting system in Light Athletic Palace, Gomel, Belarus.